4 - Social Value of Research and Technical Skills: Does It Justify Investment in Higher Education for Development? T. Paul Schultz - T. Paul Schultz, (Journal of Higher Education in Africa, 2004)
Evidence assembled from household surveys collected from 1985 and 1998 from Ghana, Côte d’Ivoire, Kenya, and South Africa indicates that higher wages compensate individuals in these African countries for enrolling in school. It is commonly believed that wage returns to schooling are highest at the primary levels and decrease thereafter at higher school levels, but the data from Africa summarized here indicate the opposite, with private wage returns being high- est at the secondary and higher education levels. There appear to be sufficient financial incentives today to motivate students to enroll in higher education, and any public subsidies should be allocated only to those students who come from poor families and whose parents are relatively least educated, relative to their generation. If students in higher education in Africa from upper-income families paid tuitions which were equal to half the public subsidies for their schooling, these revenues would finance fellowships for disadvantaged stu- dents and also provide the resources and incentives to expand higher education into those fields where trained manpower is scarcest today in Africa. They would thus create the conditions for greater self-governance of higher educa- tion while fostering a responsible separation from political power.